The acute effects of a caffeine-containing supplement on strength, muscular endurance, and anaerobic capabilities - Beck, T. W.; Housh, T. J.; Schmidt, R. J.; Johnson, G. O.; Coburn, J. W.; Malek, M. H. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to examine the acute effects of a caffeine-containing supplement on upper- and lower-body strength and muscular endurance as well as anaerobic capabilities. Thirty-seven resistance-trained men (mean ± SD, age: 21 ± 2 years) volunteered to participate in this study. On the first laboratory visit, the subjects performed 2 Wingate Anaerobic Tests (WAnTs) to determine peak power (PP) and mean power (MP), as well as tests for 1 repetition maximum (1RM), dynamic constant external resistance strength, and muscular endurance (TOTV; total volume of weight lifted during an endurance test with 80% of the 1RM) on the bilateral leg extension (LE) and free-weight bench press (BP) exercises. Following a minimum of 48 hours of rest, the subjects returned to the laboratory for the second testing session and were randomly assigned to 1 of 2 groups: a supplement group (SUPP; n = 17), which ingested a caffeine-containing supplement, or a placebo group (PLAC; n = 20), which ingested a cellulose placebo. One hour after ingesting either the caffeine-containing supplement or the placebo, the subjects performed 2 WAnTs and were tested for 1RM strength and muscular endurance on the LE and BP exercises. The results indicated that there was a significant (p < 0.05) increase in BP 1RM for the SUPP group, but not for the PLAC group. The caffeine-containing supplement had no effect, however, on LE 1RM, LE TOTV, BP TOTV, PP, and MP. Thus, the caffeine-containing supplement may be an effective supplement for increasing upper-body strength and, therefore, could be useful for competitive and recreational athletes who perform resistance training.